2017
DOI: 10.1016/j.eatbeh.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Eating in the absence of hunger during childhood predicts self-reported binge eating in adolescence

Abstract: Objective-The objectives of the current study were to examine whether eating in the absence of hunger (EAH) at age 7 predicted reports of self-reported binge eating at age 15 and to identify factors among girls with high-EAH that moderated risk of later binge eating.Method-Subjects included 158 girls assessed at age 7 and age 15. Logistic regression was used to predict binge eating at age 15 from calories consumed during EAH at age 7. A series of logistic regressions were used to examine the odds of reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 25 publications
1
27
0
2
Order By: Relevance
“…Indeed, eating in the absence of hunger at age 7 has been found to predict binge eating problems in adolescents (i.e. at age 15), with a higher BMI, dietary restraint, body dissatisfaction and negative affect elevating the risk [105]. Another recent prospective study showed that after a 1-year interval, emotional eating alone was not related to weight gain in adolescents; however, in conjunction with loss of control over eating, there was weight gain at the 1-year follow-up [106•].…”
Section: What Role Does Emotional Eating Have In the Development Of Cmentioning
confidence: 98%
“…Indeed, eating in the absence of hunger at age 7 has been found to predict binge eating problems in adolescents (i.e. at age 15), with a higher BMI, dietary restraint, body dissatisfaction and negative affect elevating the risk [105]. Another recent prospective study showed that after a 1-year interval, emotional eating alone was not related to weight gain in adolescents; however, in conjunction with loss of control over eating, there was weight gain at the 1-year follow-up [106•].…”
Section: What Role Does Emotional Eating Have In the Development Of Cmentioning
confidence: 98%
“…2 Furthermore, children who eat in the absence of hunger, who have guilty feelings about the behavior, and try to hide their overeating may develop a binge eating disorder (BED), a condition commonly associated with obesity in adults. 3,4 Identifying the prevalence and examining the determinants of binge eating symptoms in children with obesity may have important influences on reductions in eating disorders and obesity incidence and prevalence. 5 The Diagnostic and Statistical Manual of Mental Disorders (DSM-5) criteria for diagnosis of BED requires episodes of binge eating that are defined by at least three of the following symptoms: (1) eating more rapidly than normal, (2) eating until feeling uncomfortably full, (3) eating large amounts of food when not feeling physically hungry, (4) eating alone because of embarrassment by the amount of food consumed, and (5) feeling disgusted with oneself, depressed, or guilty after overeating.…”
Section: Introductionmentioning
confidence: 99%
“…This engagement may not have been as apparent in the parents receiving the resource only. Nonetheless, it is a very positive finding that children report lower External Eating possibly because their parent attended the CBCC workshop, and may enjoy lower risks for a number of adverse health outcomes into the future, including binge eating [3] and low self-esteem [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Research examining body satisfaction and unhealthy eating patterns, as well as the related issue of weight bias, increasingly suggests that the foundations of these problems are established in early childhood [1][2][3]. Consequently, identifying effective strategies to protect against these problems, early in life, would be extremely valuable.…”
Section: Introductionmentioning
confidence: 99%